(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: This Systematic review was undertaken to bring forward some solution to the old stubborn neglected problem of enuresis in children which appears to be left out in the race of scientific advancements. The pathogenesis of disease so far understood is supposed to be the result of three factors of Polyuria, Overactive bladder and difficulties in arousal from sleep. However pinpointing the extent and role of each one in an individual case is a difficult time and resource consuming job. The aim of study is to help front line clinicians in decision making in poor resource limited developing countries, so that children and families are not abandoned to suffer on their own without any hope for a speedy solution, when they come forward asking for help. Methods: We hypothesized that combination therapy of Desmopressin and oxybutynin in usual therapeutic doses at outset, might be a solution. To accumulate evidence an extensive search was done as per PRISMA 2020 guideline for properly designed double blind Randomized clinical trials to back up any such decision. Databases searched were PubMed, Embase, Google Scholar, Scopus and web of science. Clinical trial registry platforms, open access grey areas and cross references were also searched. Data obtained was analyzed by random effect model , at 95% confidence interval with Mantel Haenszel test for risk ratio. Protocol was registered at PROSPERO Results: There was lack of robust randomized data for any nodal network meta-analysis. Nine studies were included for analysis having experimental or Intervention arm as combination therapy versus Desmopressin mono drug therapy as comparator. Synthesis of data and meta-analysis was done using Cochrane Revman version 5.4 There was lack of studies for comparison to Oxybutynin and Imipramine mono drug therapy, hence they are discussed in tabular form only There is some hope in other combinations also in new entrants in the armamentarium against enuresis in children like Tolterodine, Solifenacin, Propiverine. A favorable outcome was observed for this combination therapy at outset in whatever studies we found, but risk of bias is there and superiority can be said as only marginal. More robust evidence is needed from scientific researchers for different pharmacological combination therapies at outset to decrease the gap from the point of seeking help to control of enuresis. Conclusion: We recommend trial of Desmopressin Oxybutynin combination therapy at the time of seeking help in resource poor developing countries to tackle this stigmatized socially unacceptable problem of children at present. This will also help in generating more robust data in favor or against any such decision for future reference and analysis. But we can say that the scientific fraternity is still far behind in properly designed randomized and blinded trials for any clear and evidence based medicine for this entity. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 685-697